2019
DOI: 10.1590/0034-7167-2018-0137
|View full text |Cite
|
Sign up to set email alerts
|

Elderly caregivers of the elderly: frailty, loneliness and depressive symptoms

Abstract: Objective: to investigate the association between frailty, loneliness and depressive symptoms of elderly caregivers. Method: a cross - sectional study carried out with 341 elderly caregivers enrolled in Family Health Units of a city in the countryside of São Paulo State. The interviews were domiciliary and included questionnaire for characterization of the caregiver, Fried’s frailty phenotype, family APGAR (family functionality), Geriatric Depression Scale (depressive symptoms) and item 3 of the Herth Hope Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 45 publications
3
13
1
9
Order By: Relevance
“…Therefore, not being married generally leads older adults to live alone, which can promote loneliness, especially during periods of social isolation and, consequently, generate depressive 11/15 symptoms. This perspective is in line with a study on older adults who cared for other older adults, which revealed that those who were lonely caregivers and who had depressive symptoms were more likely to develop fragility, as they felt less fortunate to participate in groups, interact with other people and practice physical activities, which directly impacts physical health and psychological well-being, 25 as in COVID-19 times.…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, not being married generally leads older adults to live alone, which can promote loneliness, especially during periods of social isolation and, consequently, generate depressive 11/15 symptoms. This perspective is in line with a study on older adults who cared for other older adults, which revealed that those who were lonely caregivers and who had depressive symptoms were more likely to develop fragility, as they felt less fortunate to participate in groups, interact with other people and practice physical activities, which directly impacts physical health and psychological well-being, 25 as in COVID-19 times.…”
Section: Discussionsupporting
confidence: 83%
“…Quando questionados sobre como se tornaram cuidadores, em geral, as respostas demonstram o inusitado da nova situação que tiveram que assumir, sem dar ouvidos às próprias frustrações e angústias que a partir de então os invadiram 13,14 . A expressão eu tenho que me controlar ao extremo, denuncia a habilidade que desenvolveram de inibir as emoções num contexto de desamparo ou de ausência de reconhecimento e apoio.…”
Section: Movimentos De Inibição De Sentimentos E Emoçõesunclassified
“…Os resultados evidenciam alto índice de cuidadores com sintomas depressivos de leve a moderado, detectados pelas escalas de HAM-D e MADRS, muito acima do encontrado na literatura (Santos-Orlandi et al, 2019;Terassi, Rossetti, Luchesi, Gramani-Say, Hortense, & Pavarini, 2020). Em nosso estudo, 31,3% dos entrevistados relataram diagnóstico prévio, e dos que referiram não possuir, apenas um não apresentou resultados para sintomatologia depressiva na HAM e MADRS.…”
Section: Discussionunclassified